Knowledge Enhancement and Understanding of Diversity - Tiwari, Siddhartha Paul (Technium Social Sciences Journal, 2022)
In many societies, diversity has been neglected. The importance of diversity in the society for knowledge generation has become increasingly apparent in recent years. In order to achieve diversity, we need to take into account people from various backgrounds and backgrounds, and to understand that every individual is unique. Differentiating people can be based on race or ethnicity, nationality, age, gender, sexual orientation, economic background, and disabilities. We must recognize that each of these differences results in different experiences for individuals, and that all of these experiences can be synthesized to generate knowledge that is both more inclusive and more comprehensive. Diverse initiatives can be used to promote diversity in educational institutions, such as affirmative action and diversity programs. As diversity enhances receptivity to learning from others’ experiences, it is essential for creativity and innovation. Furthermore, diversity promotes productivity and performance as a team can draw on the experience of each individual to find solutions to problems. Individuals must be aware of different opportunities and possibilities in order to grow as individuals, and diversity allows this to happen. As diversity prepares individuals for a diverse world, it is also important to students’ learning. Ultimately, diversity contributes significantly to the creation of new knowledge due to the fact that it helps people draw on their own experiences and the experiences of others in order to discover new approaches to problems.